CRISPR/Cas13d-Mediated Microbial RNA Knockdown - Zhang, Kun; Zhang, Zhihui; Kang, Jianan; Chen, Jiuzhou; Liu, Jiao; Gao, Ning; Fan, Liwen; Zheng, Ping; Wang, Yu; Sun, Jibin (Frontiers in Bioengineering and Biotechnology, 2020)
RNA-guided and RNA-targeting type IV-D CRISPR/Cas systems (CRISPR/Cas13d) have recently been identified and employed for efficient and specific RNA knockdown in mammalian and plant cells. Cas13d possesses dual RNase activities and is capable of processing CRISPR arrays and cleaving target RNAs in a protospacer flanking sequence (PFS)-independent manner. These properties make this system a promising tool for multiplex gene expression regulation in microbes. Herein, we aimed to establish a CRISPR/Cas13d-mediated RNA knockdown platform for bacterial chassis. CasRx, Cas13d from Ruminococcus flavefaciens XPD3002, was selected due to its high activity. However, CasRx was found to be highly toxic to both Escherichia coli and Corynebacterium glutamicum, especially when it cooperated with its guide and target RNAs. After employing a low copy number vector, a tightly controlled promoter, and a weakened ribosome binding site, we successfully constructed an inducible expression system for CasRx and applied it for repressing the expression of a green fluorescent protein (GFP) in E. coli. Despite our efforts to optimize inducer usage, guide RNA (gRNA) architecture and combination, and target gene expression level, the highest gene repression efficiency was 30–50% at the protein level and ∼70% at the mRNA level. The moderate RNA knockdown is possibly caused by the collateral cleavage activity toward bystander RNAs, which acts as a mechanism of type IV-D immunity and perturbs microbial metabolism. Further studies on cellular response to CRISPR/Cas13d and improvement in RNA knockdown efficiency are required prior to practical application of this system in microbes.